Advancing the field of communication research in pediatric oncology: A systematic review of the literature analyzing medical dialogue. Issue 12 (1st August 2018) - Kaye, Erica C.; Kiefer, Ashley; Zalud, Kristina; Gattas, Melanie; Snyder, Ian; Spraker‐Perlman, Holly; Baker, Justin N.
Abstract: Historically, communication research in pediatric oncology has relied on surveys and interviews, resulting in cross‐sectional and retrospective studies constrained by selection, recognition, and recall biases. This systematic review identifies and synthesizes the published literature analyzing primary data from recorded conversations between pediatric oncologists, patients with cancer, and their families, with the following objectives: (1) to identify the extent and content of the evidence base, (2) to describe methodological strategies utilized in the analysis of recorded medical dialogue, (3) to aggregate salient findings, and (4) to generate recommendations for future prospective research related to analysis of medical dialogue in pediatric oncology.